Antifascist Front and military politics of the Communist Party of Chile under dictatorship, 1973-1980 - Silva, Claudio Pérez (Revista Tempo e Argumento, 2016)
This article inquires about the route of the military politics of the Communist Party of Chile, particularly under its political commitment to the Antifascist Front (1973-1980). In this regard, we argue that, in a first stage, this party pursued its military politics primarily based on evaluations about the causes of Allende’s defeat. This implied an almost unrestricted continuity of its military politics during the early years of dictatorship. However, after the first measures taken in order to palliate its shortcomings, and also face the imminent extension and institutionalization of dictatorship, there was a slow, but significant expansion of its military politics in the late 1970s, a dynamics that ended up contributing both to the political reconfiguration of its militancy and its commitment to bring the dictatorship to an end.